Winning Strategy and Factors Affecting Win In The Village Head Election Contest (Pilkades): Case Study In Sengon Village, Tanjung Subdistrict, Brebes Regency - Maldini Faqih (Journal of Law and Social Politics, 2023)
The election of a candidate for a leader who is the embodiment of democracy is interpreted as one of the people's parties whose presence is eagerly awaited. Of course, in its implementation, it also causes euphoria, commotion, pleasure, happiness, or even sadness and pain. It is no different with the holding of village head elections (pilates) which are held every six years, where there are interesting things in its implementation that need to be studied and discussed. This writing aims to find out the ins and outs of what happens during the big village community democracy celebration party (parkades), more specifically about how the winning strategy is and the factors that influence victory during the parkades contestation. The method that the author uses in this paper is a qualitative research method. The results of this study can be obtained that in the implementation of the parkades, the strategies of the candidates and their teams when struggling to make efforts to win against them, can be done in several ways, including political mapping, forming a core success team, or core cadre ranks, staying in touch with religious leaders. and local community leaders, and others. In addition, several factors influence victory in a village head election contestation, including internal factors of candidates, investors, political contracts and politics of reciprocation, money politics, gambling, and others.